Model Pembelajaran Kooperatif Tipe STAD Berbantuan Handout Pengaruhnya Terhadap Kompetensi Siswa - Yurnalisma Dewi (EDU-BIO: Jurnal Pendidikan Biologi, 2023)
The Problems of this research were (1) the learning process was still dominated by the teacher (lecturing method); (2) the students got difficulties to understand the learning materials; (3) the students’ average score was below the minimum standard score 65; (4) the students werw less competent on effective and psychomotor aspects. The aim of this study was written to determine differences in cognitive learning competencies, affective, and psychomotor of the students who take STAD cooperative learning model aided with handout toward cognitive, affective, and psychomotor of the students who take conventional learning. This was a quasi experimental research. The population of this research was the students in class X of SMAN 3 Desa Empelu registered in Academic Year 2014/2015. By using random sampling technique, the students in class X2 was chosen an the experimental class, and those in class X1 was taken of 40 item which had been tried out previously, and observation sheet. The data was analyzed by using t-test and Mann Whitney U test. The result of the research indicated that the average score of the students on cognitive aspect in the experimental class was higher than that in the control class. The students’ competence on effective aspect in the experimental class was good, and in the control class was fair. The students’ competence on psychomotor aspect in the experimental class was good, and in the control class was fair. Thus, the use of STAD cooperative learning model assisted with handout affected the students’ learning competence in Biology at SMAN 3 Desa Empelu Keywords : Cooperative Learning Model, STAD, Handout, Student Competency